Barriers to Adequate Prenatal Care in Managing Anemia among Pregnant Women - Dar, Aliya; Asadullah Jan, Hoor; Ahmad, Sadia; Zulfiqar, Nadia; Firdous, Tabassum; Ahmad Danial, Mubeen; Jadoon, Shandana Mustafa (Journal of Neonatal Surgery, 2025)
Background: Anemia during pregnancy is a significant public health issue, particularly in low- and middle-income countries. Despite efforts to address anemia, barriers to adequate prenatal care remain a critical challenge in managing this condition. Objective: To assess the prevalence of anemia among pregnant women and evaluate the association of sociodemographic and healthcare access barriers with anemia status. Material and Methods: This cross-sectional study was conducted at the Department of Obstetrics and Gynecology, Saeed Medical Complex, Mattani, Peshawar, from January 2024 to June 2024. A total of 361 pregnant women attending antenatal care services were included. Sociodemographic characteristics, healthcare access barriers, awareness of anemia, and compliance with iron supplementation were assessed using a structured questionnaire. Hemoglobin levels were retrieved from medical records, and anemia was classified based on World Health Organization (WHO) criteria. Data were analyzed using descriptive statistics, Chi-Square tests, and independent t-tests, with a p-value <0.05 considered statistically significant. Results: The mean age of participants was 30.47 years (SD = 7.085), and the mean hemoglobin level was 10.45 g/dL (SD = 1.683). The prevalence of anemia was 44.6%, with 161 participants classified as anemic and 200 as non-anemic. Anemia prevalence varied across education, socioeconomic status, parity, distance to healthcare, and other barriers, but no statistically significant associations were observed (p > 0.05). Conclusion: Anemia remains a prevalent issue among pregnant women, with multiple potential barriers contributing to its management. Despite non-significant associations, these barriers highlight areas for targeted interventions to improve prenatal care and anemia outcomes.